Cryptography Algorithms : A Guide to Algorithms in Blockchain, Quantum Cryptography, Zero-Knowledge Protocols, and Homomorphic Encryption - Bertaccini, Massimo (Packt Publishing, Limited, 2022)
Build your real-world cryptography knowledge, from understanding the fundamentals to implementing the most popular modern-day algorithms to excel in your cybersecurity career Key Features Learn modern algorithms such as zero-knowledge, elliptic curves, and quantum cryptography Explore vulnerability and new logical attacks on the most-used algorithms Understand the practical implementation of algorithms and protocols in cybersecurity applications Book Description Cryptography Algorithms is designed to help you get up and running with modern cryptography algorithms. You'll not only explore old and modern security practices but also discover practical examples of implementing them effectively. The book starts with an overview of cryptography, exploring key concepts including popular classical symmetric and asymmetric algorithms, protocol standards, and more. You'll also cover everything from building crypto codes to breaking them. In addition to this, the book will help you to understand the difference between various types of digital signatures. As you advance, you will become well-versed with the new-age cryptography algorithms and protocols such as public and private key cryptography, zero-knowledge protocols, elliptic curves, quantum cryptography, and homomorphic encryption. Finally, you'll be able to apply the knowledge you've gained with the help of practical examples and use cases. By the end of this cryptography book, you will be well-versed with modern cryptography and be able to effectively apply it to security applications. What you will learn Understand key cryptography concepts, algorithms, protocols, and standards Break some of the most popular cryptographic algorithms Build and implement algorithms efficiently Gain insights into new methods of attack on RSA and asymmetric encryption Explore new schemes and protocols for blockchain and cryptocurrency Discover pioneering quantum cryptography algorithms Perform attacks on zero-knowledge protocol and elliptic curves Explore new algorithms invented by the author in the field of asymmetric, zero-knowledge, and cryptocurrency Who this book is for This hands-on cryptography book is for IT professionals, cybersecurity enthusiasts, or anyone who wants to develop their skills in modern cryptography and build a successful cybersecurity career. Working knowledge of beginner-level algebra and finite fields theory is required.